(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the role of nonverbal means in the process of communicative communication in Russian and how they are used in a cultural context. In particular, the importance of nonverbal elements in communication, such as facial expressions, body movements, tone of voice, distance, and physical contact, is analyzed. Information is provided on the role of nonverbal signs specific to Russian culture in effective communication, and the importance of the correct interpretation of these means for language learners is emphasized.